Role of the foreign bank representative office to encourage foreign direct investment inflow increasement in Indonesia - Aryati, Yustia; Hendranastiti, Nur Dhani (Institute of Computer Science (IOCS), 2024)
Offshore loans to Indonesian borrowers are essential for financing large-scale investment projects in Indonesia. This research uses a mixed method between case studies and Spearman Rank correlation tests. The qualitative approach was through interviews to collect research data and continued with a quantitative approach using the Spearman Rank correlation test. The study found that during 2017 and 2022, there are offshore loans were used for project financing with sector similarities with greenfield FDI inflows and international project finance. Also, there were representative offices actively involved in the M&A process of a national bank in 2022 and a Multi finance company in 2020. This research fills a knowledge gap regarding the role of foreign bank representative offices concerning FDI inflows in Indonesia.